Cold water immersion improves recovery of sprint speed following a simulated tournament. Issue 9 (21st October 2019) - Leeder, Jonathan D. C.; Godfrey, Matthew; Gibbon, Daniel; Gaze, David; Davison, Gareth W.; Van Someren, Ken A.; Howatson, Glyn
Abstract: It is a common requirement in tournament scenarios for athletes to compete multiple times in a relatively short time period, with insufficient recovery time not allowing full restoration of physical performance. This study aimed to develop a greater understanding of the physiological stress experienced by athletes in a tournament scenario, and how a commonly used recovery strategy, cold water immersion (CWI), might influence these markers. Twenty-one trained male games players (age 19 ± 2; body mass 78.0 ± 8.8 kg) were randomised into a CWI group ( n = 11) or a control group ( n = 10). To simulate a tournament, participants completed the Loughborough Intermittent Shuttle Test (LIST) on three occasions in five days. Recovery was assessed at specific time points using markers of sprint performance, muscle function, muscle soreness and biochemical markers of damage (creatine kinase, CK), inflammation (IL-6 and C-Reactive Protein) and oxidative stress (lipid hydroperoxides and activity of 6 lipid-soluble antioxidants). The simulated tournament was associated with perturbations in some, but not all, markers of physiological stress and recovery. Cold water immersion was associated with improved recovery of sprint speed 24 h after the final LIST (ES = 0.83 ± 0.59; p = .034) and attenuated the efflux of CK pre- and post-LIST 3 ( p < .01). The tournament scenario resulted in an escalation of physiological stress that, in the main, cold water immersion was ineffective at managing. These data suggest that CWI is not harmful, and provides limited benefits in attenuating the deleterious effects experienced during tournament scenarios.